Primary non-communicable disease prevention and communication barriers of deaf sign language users: a qualitative study - Severin Pinilla; Sebastian Walther; Arnd Hofmeister; Soeren Huwendiek (BMC, 2019)
Abstract Background Deaf sign language users have lower health literacy and poorer access to non-communicable disease prevention information as compared to the general population. The aim was to explore disease concepts embedded in signs, primary non-communicable disease prevention behaviour and communication barriers among members of a deaf community. Methods A qualitative study with a social constructivist approach was conducted to explore perspectives of deaf sign language users.15 individuals, two with and 13 without history of diabetes were recruited for semi-structured in-depth interviews in sign language at a deaf community center. The interviews were video-recorded, translated and analyzed using thematic content analysis. Results Diabetes as one of the main non-communicable diseases is conceptualized differently in the manual component of signs depending on how deaf sign language users construct diabetes pathophysiologically. The disease conceptualization is not represented in the mouthing component. Health information seeking behavior varies among deaf sign language users and depends on their individual spoken and written language literacy. Overcoming communication barriers is key for developing an understanding of diabetes and other non-communicable disease prevention activities. Conclusions To develop barrier-free and inclusive non-communicable disease and diabetes prevention strategies for deaf sign language users, health professionals need to pay attention to sign language specific linguistic concepts. More studies are needed to better understand the specific needs of sign language users and effective strategies in health promotion contexts for sign language users.